Induction of remission in a patient with Takayasu's arteritis by low dose pulses of methotrexate. Issue 7 (July 1992) - Mevorach, D; Leibowitz, G; Brezis, M; Raz, E
Abstract : A 42 year old woman with Takayasu's arteritis responded to treatment with prednisone (60 mg daily) but developed severe side effects. Cyclophosphamide treatment did not produce a clinical improvement or steroid sparing effect. A treatment trial with a weekly pulse of low dose methotrexate improved her symptoms and the patency of her occluded left subclavian artery.